NEW SPECIES OF SARCINELLA FROM INDIA - REETA CHAUDHARY, SATISH CHANDRA, NEERAJ SRlVASTAVA AND (Indian Phytopathology, 2002)
Three species of Sarcinella Sacc., viz., S. bignoniacearum sp. nov., S. indica sp. \ novo and S. jarwaensis sp. novo collected on Oroxylum indicum Vent. (Bignoniaceae), Sapium insigne Trim. (Euphorbiaceae) and Terminalia che.bula Retz. (Combretaceae), from three different localities of this country are described and illustrated.